Effects of various chemical modifiers on the determination of arsenic by electrothermal atomic absorption spectrometry and application to the solid samples - Akdeniz, I; Yaman, M (Asian Journal of Chemistry, 2005)
Various chemical matrix modifiers were studied for arsenic determination by platform atomization-ETAAS. The studied matrix modifiers include the nitrate salts of palladium, iron, molybdenum and nickel and the mixture. of Ni + triton X-100. Palladium modifier was found the best reagent in comparison with other studied modifiers. The optimized methods were applied to the determination of arsenic in solid samples such as soil, coal, coal-bottom ashing and coal fly ashing, the slag of copper mining and cement raw materials such as clay, gypsum and calcareous samples taken from east of Turkey. Very high concentration of arsenic was found in copper slag as high as 10500 mg kg(-1).
Keywords: chemical modifier; GFAAS; arsenic; solid samples; fly ashing